Exploring influences on intended evacuation behaviors during wildfire: What roles for pre-fire actions and event-based cues?. (July 2019) - Edgeley, Catrin M.; Paveglio, Travis B.
Highlights: We analyzed survey data from 1, 349 households in McCall, Idaho. Analysis explored intended evacuation behaviors and cues influencing such actions. Pre-fire and event-based cues were correlated with specific intended behaviors. A group of respondents had no evacuation plans and were not influenced by any cues. Flexible guidance that incorporates dynamic cues could improve evacuation planning.